Minimal lamellar structures in a periodic FitzHugh–Nagumo system. (May 2020) - Acerbi, Emilio; Chen, Chao-Nien; Choi, Yung-Sze
Abstract: A singular limit of a FitzHugh–Nagumo system leads to a nonlocal geometric variational problem with periodic boundary conditions. We study the stationary lamellar set and give a criterion to select out the one with the lowest energy. Such an optimal structure is called a minimal lamella. While the empty set or the full torus is a global minimizer for appropriate parameter regimes, the minimal lamellae beat both in other circumstances. The concept of minimal lamella points out that a preferred 1D mesh size is universal.